Economic Evaluation Alongside a Randomized Controlled Crossover Trial of Modified Group Cognitive–Behavioral Therapy for Anxiety Compared to Treatment-as-Usual in Adults With Asperger Syndrome. Issue 2 (August 2017) - Doble, Brett; Langdon, Peter E.; Shepstone, Lee; Murphy, Glynis H.; Fowler, David; Heavens, David; Malovic, Aida; Russell, Alexandra; Rose, Alice; Mullineaux, Louise; Wilson, Edward C. F.
Background: There is a growing interest in using group cognitive–behavioral therapy (CBT) with people who have Asperger syndrome (AS) and comorbid mental health problems. This study aims to assess the cost-effectiveness of modified group CBT for adults with AS experiencing co-occurring anxiety compared to treatment-as-usual.Methods: Economic evaluation alongside a pilot, multicenter, single-blind, randomized controlled crossover trial. Costs from the UK public sector (National Health Service and Social Services) and societal perspectives, quality-adjusted life years (QALYs), incremental net (monetary) benefit (INB), expected value of perfect information, expected value of sample information, expected net gain of sampling, and efficient sample size of a future trial are reported.Results: Over 48 weeks, from the societal perspective, CBT results in additional costs of £6, 647, with only a 0.015 incremental gain in QALYs, leading to a negative INB estimate of £6, 206 and a 23% probability of cost-effectiveness at a threshold of £30, 000/QALY. Results from sensitivity analyses support the unlikely cost-effectiveness of CBT but indicate the potential for cost-effectiveness over longer time horizons. Eliminating decision uncertainty is valued at £277 million, and the efficient sample size for a future trial is estimated at 1, 200 participants per arm.Limitations: Relatively small sample size and prevalence of missing data present challenges to the interpretation of the results.Conclusions: Current evidence from this small pilot study suggests that, on average, modified group CBT is not cost-effective. However, there is much decision uncertainty so such a conclusion could be wrong. A large, full-scale trial to reduce uncertainty would be an efficient investment for the UK health economy.